Diagnostic Role of Image-Guided Fine Needle Aspiration Cytology - Sherpa, Palzum; Koirala, Sudhamsu (Nepalese Medical Journal, 2022)
Introduction: With the aid of modern imaging procedures like ultrasonography and computed tomography, fine needle aspiration cytology of deeper structures, small and vaguely palpable swellings, and lesions that are in close proximity to major vasculature are feasible. This study aims to establish the prevalence of image-guided FNAC, evaluate its diagnostic utility, and assess the spectrum of disorders diagnosed with its usage. Materials and Methods: A retrospective descriptive study was performed in the Pathology department, Om Hospital, and Research Centre from May 2015 to November 2019. The study included all samples of image-guided FNACs which were received for cytological examination. Results: Image-guided FNAC accounted for 13.03% of all FNACs done during the study period. Female predominance with a male to female ratio of 1:1.4 was noted. The age of the patients ranged from 13 to 85 years with a mean age of 53.6 years. The majority of the FNACs were performed under USG guidance. The lung was the most commonest site followed by lymph nodes and liver. Cytological diagnosis was made in 225 (88.93%) of the total cases. 7 (2.77%) cases were suspicious for malignancy and 21 (8.3%) were inconclusive. The majority of the lesions were categorized as malignant. Conclusions: Image-guided FNAC has a good diagnostic yield for deeper structures and small and vaguely palpable swellings. A spectrum of lesions, both neoplastic and non-neoplastic can be diagnosed with its usage. The commonest site of aspiration was the lung followed by lymph nodes and liver.